2008
DOI: 10.1590/s1516-35982008001100020
|View full text |Cite
|
Sign up to set email alerts
|

Consórcio capim-braquiária e soja, produtividade das culturas e características qualitativas das silagens

Abstract: RESUMO -Objetivou-se avaliar o cultivo de capim-braquiária e soja em consórcio ou exclusivamente. Avaliaram-se a produção de matéria seca (MS) e os teores de proteína bruta (PB) e nutrientes digestíveis totais (NDT) por hectare; os teores de proteína bruta, fibra em detergente neutro (FDN), lignina (LIG), carboidratos não-fibrosos (CNF), NDT, ácido butírico e ácido lático; o nitrogênio amoniacal; o teor de MS e o pH das silagens dessas culturas colhidas em dois estádios fenológicos (R 6 e R 7 ) das plantas de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
4
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 15 publications
1
4
4
3
Order By: Relevance
“…For Kung Jr. and Shaver (2001), the pH of legume silages with 30% DM and perennial temperate grass silage ranges from 4.3 to 4.7. Other studies (Leonel et al, 2008;Souza et al, 2014;Silva et al, 2014) have shown similar values to that observed in the present work for this characteristic.…”
Section: Journal Of Agricultural Sciencesupporting
confidence: 93%
See 1 more Smart Citation
“…For Kung Jr. and Shaver (2001), the pH of legume silages with 30% DM and perennial temperate grass silage ranges from 4.3 to 4.7. Other studies (Leonel et al, 2008;Souza et al, 2014;Silva et al, 2014) have shown similar values to that observed in the present work for this characteristic.…”
Section: Journal Of Agricultural Sciencesupporting
confidence: 93%
“…The lower fiber contents in legumes in relation to tropical grasses are explained mainly by the physiological differences between them, being the marandu grass a C4 specie and the leguminous C3. Differences in fiber content between grass and legume silages were also observed by Leonel et al (2008) and Silva et al (2015), this result is an indicative of higher digestibility and, consequently, better nutritive value of the silages with legume.…”
Section: Journal Of Agricultural Sciencementioning
confidence: 63%
“…Silages of legume alone have poor quality due to high buffering power and low soluble carbohydrate content (Lima, Lourenço, Díaz, Castro, & Fievez, 2010). Nevertheless, the use of legumes mixed with grasses improves the quality of the ensiled mass and increases the protein content when compared to the silage of corn or sorghum alone (Leonel et al, 2008;Lima-Orozco, Castro-Alegría, & Fievez, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Entretanto, o teor de proteína não seria a única causa de tamponamento, uma vez que minerais como o cálcio podem também contribuir com íons nos sistemas tampões. Leonel et al (19) , ao avaliarem as características qualitativas de vários tipos de silagens, concluíram que os elevados teores de proteína e MM dificultam a conservação da silagem, em decorrência do aumento da concentração de amônia e elevada capacidade tamponante. Além desses fatores, as características microbiológicas do soro de leite podem influenciar diretamente nas produções de gases e perdas na MS da silagem.…”
Section: Resultsunclassified
“…Segundo Ramos et al (30) , os lipídios provenientes da silagem de resíduo de tilápia podem reduzir a excessiva solubilização da proteína no material, contudo, a presença de óleo juntamente aos altos níveis de ácidos graxos poli-insaturados, que estão sujeitos à oxidação, pode tornar a silagem não palatável e imprópria ao consumo do animal. Além disso, altas concentrações de PB prejudicam a conservação da silagem devido à alta concentração de amônia no material e alteração da capacidade de tamponamento (19) .…”
Section: Resultsunclassified